Pengaruh Lama Penyimpanan Terhadap Sifat Fisik Wafer Ransum Komplit Berbasis Limbah Kol Berperekat Molases - Edelina Christmas; Yatno; Akmal Akmal; Saitul Fakhri; Suparjo Suparjo (Jurnal Ilmu dan Industri Peternakan, 2022)
This study aims to determine the effect of storage periods that doesn’t have a negative effect on the physical characteristics of wafer complete ration based on cabbage waste with molasses adhesive. The material used consists of a source of fiber and concentrate with a balanced ratio (50:50). This study used a completely randomized design (CRD) with 4 treatments, namely: WRK-0 (without storage/control), WRK-2 (2 weeks storage), WRK-4 (4 weeks storage), WRK-6 (6 weeks storage) each treated 5 times. The observed variables were density, specific gravity, and water absorption. Analysis of the data using analysis of variety (ANOVA) and if there is a significant difference with the observed changes using the Orthogonal Polynomial (PO) test. The results showed that storage time had a very significant (P<0.01) linear effect on water absorption (260-279%) with the equation Y= 259.1 + 3.3X and R2 = 0.981 but had no significant effect (P> 0.05) to the value of wafer density (0.62-0.65 g/cm3) and specific gravity (1.12-1.22 g/mL). Based on the results of the study, it was found that storage for up to 6 weeks didn’t have a negative effect on the physical characteristiscs quality of water complete ration based on cabbage waste with molasses adhesive.